2021
DOI: 10.1002/asi.24585
|View full text |Cite
|
Sign up to set email alerts
|

The data paper as a sociolinguistic epistemic object: A content analysis on the rhetorical moves used in data paper abstracts

Abstract: The data paper is an emerging academic genre that focuses on the description of research data objects. However, there is a lack of empirical knowledge about this rising genre in quantitative science studies, particularly from the perspective of its linguistic features. To fill this gap, this research aims to offer a first quantitative examination of which rhetorical moves-rhetorical units performing a coherent narrative function-are used in data paper abstracts, as well as how these moves are used. To this end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Prior investigations of data references have restricted their analysis to specific elements of literature (e.g., abstracts) or types of works (e.g., data papers) [36,46]. Manual approaches to study data references are time and resource-intensive, and do not easily scale [47].…”
Section: Related Work 21 Tracing the Impact Of Research Data In Schol...mentioning
confidence: 99%
“…Prior investigations of data references have restricted their analysis to specific elements of literature (e.g., abstracts) or types of works (e.g., data papers) [36,46]. Manual approaches to study data references are time and resource-intensive, and do not easily scale [47].…”
Section: Related Work 21 Tracing the Impact Of Research Data In Schol...mentioning
confidence: 99%
“…It also makes authors' data comprehensible and citable. An unique advantage of DIB publication records is the 'related research article' search option that links data papers to related research articles that use the datasets described in the data papers (Li & Jiao, 2021). The relationship between a data paper and a related research article provides an opportunity for us to explore how they can influence each other.…”
Section: Key Pointsmentioning
confidence: 99%
“…The distinction between data papers and certain academic publication categories is partially blurred, especially when compared to traditional research papers, as both genres emerge within similar social norms and contexts of scientific knowledge production, such as the peer review system (Li & Jiao, 2022). With the continuous development of data papers, researchers have approached and delineated the concept from various perspectives.…”
Section: Data Papersmentioning
confidence: 99%
“…She found that data journals focus more on data production information (data collection, data producers, and projects) than on general dataset properties or repository information. Li and Jiao (2022) devised a classification scheme for rhetorical moves in data paper abstracts to provide a quantitative analysis of the rhetorical moves employed in data paper abstracts and their usage patterns. The study revealed that data papers published in "Scientific Data" and "Data in Brief" display a combination of introduction, method, results, and discussion-oriented moves as well as data-oriented moves.…”
Section: Data Papersmentioning
confidence: 99%